Shifting paradigms in primary aldosteronism: reconsideration of screening strategy via integrating pathophysiological insights - Kitamoto, Takumi; Ruike, Yutaro; Koide, Hisashi; Inoue, Kosuke; Maezawa, Yoshiro; Omura, Masao; Nakai, Kazuki; Tsurutani, Yuya; Saito, Jun; Kuwa, Katsuhiko; Yokote, Koutaro; Nishikawa, Tetsuo (Frontiers in Endocrinology, 2025)
Several decades have passed since the description of the first patient with primary aldosteronism (PA). PA was initially classified in two main forms: aldosterone-producing adenoma (APA) and idiopathic hyperaldosteronism (IHA). However, the pathogenesis of PA has now been shown to be far more complex. For this reason, the traditional classification needs to be updated. Given the recent advancements in our understanding of PA pathogenesis, we should reevaluate how frequent PA cases are, beginning with the reconstruction of the screening strategy. Recent studies consistently indicated that PA has been identified in 22% of patients with resistant hypertension and 11% even in normotensives. The frequency is influenced by the screening strategy and should be based on understanding the pathogenesis of PA. Progress has been made to promote our understanding of the pathogenesis of PA by the findings of aldosterone driver mutations, which have been found in normotensives and hypertensives. In addition, much clinical evidence has been accumulated to indicate that there is a spectrum in PA pathogenesis. In this review, we will summarize the recent progress in aldosterone measurement methods based on LC-MS/MS and the current screening strategy. Then, we will discuss the progress of our understanding of PA, focusing on aldosterone driver mutations and the natural history of PA. Finally, we will discuss the optimal strategy to improve screening rate and case detection.